Chronic localised encephalitis (Rasmussen's) in an adult with epilepsia partialis continua. Issue 6 (June 1987) - Gray, F; Serdaru, M; Baron, H; Daumas-Duport, C; Loron, P; Sauron, B; Poirier, J
Abstract : A 29 year old male presented with epileptic fits, progressive left sided focal seizures and epilepsia partialis continua, increasing left hemiparesis and mental slowing. Death occurred 2 years after the onset of the illness. Lesions were limited to the right cerebral hemisphere. Hypertrophic astrocytosis was diffuse throughout the gray and white matter but was more severe in the deep cortical layers and U fibres, where it was associated with vacuolar changes and capillary proliferation. Sparse perivascular lymphocytic cuffs, rod shaped microglia and microglial nodules were present. No inclusion bodies were found. These clinico-pathologic features were similar to the cases described by Rasmussen. Only five necropsy cases of this rare disease have been reported previously, all in children. The aetiology is unknown.